Assessing the need for technology-enhanced tools to release the sufferings of Cinderella in language teaching (Pronunciation) - Suwartono, Tono; Nurhayati, Sri; Junaid, Rusdiana (Edelweiss Applied Science and Technology, 2024)
Pronunciation appears to be the most marginalized topic in the curriculum and classroom practices of English as a foreign language at all levels of education, leading to the minimum performance of students in pronouncing English words. The present study investigates the learning problems, teaching practices and needs for media related to the English pronunciation teaching and learning in higher education. It was a survey study participated by 293 university students across departments and faculties at a private university in Indonesia. Data were gathered using a self-administered 5-point Likert scale questionnaire and analysed using descriptive statistics. Results of the study revealed that the university students consider English as a difficult subject. Regarding pronunciation, for them it is considered a complicated aspect to acquire although they perceive their English pronunciation as relatively good. Most students claimed that their English teachers never teach them pronunciation in specific and reported that the teachers mostly use tape-player for teaching pronunciation and seem lowly involved in empowering technology-enhanced instructional facilities. It is obvious that the students need more interesting and practical media to learn English pronunciation. Evidence from this study indicates that regarding English pronunciation the students can be trained intensively with more practical media that facilitate English pronunciation learning.